14 THE DUAL SRC/ABL KINASE INHIBITOR SKI-606 EFFECTIVELY INHIBITS BCR-ABL KINASE ACTIVITY IN CHRONIC MYELOGENOUS LEUKEMIA PRIMITIVE PROGENITOR CELLS. Issue 1 (1st January 2007) - Sindhu, S.; Koenig, H.; Boschelli, F.; Holyoake, T. L.; Forman, S. J.; Bhatia, R.
Abstract : Chronic myelogenous leukemia (CML) is a hematopoietic stem cell malignant disease that results from a translocation between chromosomes 9 and 22. The translocation generates the BCR/ABL gene, which has been shown to play a role in the pathogenesis of CML. Imatinib mesylate (IM), a Bcr-Abl kinase inhibitor, is highly effective in the treatment of CML. However CML stem cells appear to be relatively resistant to elimination by IM. Incomplete elimination of malignant progenitors may be related to incomplete Bcr-Abl kinase inhibition, persistent signaling through MAPK, or Bcr-Abl kinase mutations resulting in IM resistance. This phenomenon creates a need to develop new approaches that enhance elimination of the malignant progenitor cells. The dual Src/Abl kinase inhibitor SKI-606 has been reported to exert potent antiproliferative activity against CML cell lines in vitro and in xenograft models and is currently being investigated in phase 1/2 clinical trials. CD34 + CD38 − primitive progenitor and CD34 + CD38 + committed progenitor cells from untreated CML patients were selected by flow cytometry and then cultured for 24 hours in growth factor-supplemented medium in a range of concentrations of SKI-606 (0-0.5 μM) and with 5 μM IM for comparison. The effect of SKI-606 on Bcr-Abl-kinase activity was assessed by Western blotting with anti-P-CrkL antibodies after overnight drug exposure of CML CD34 + cells. Importantly, 0.1 μM and 0.5 μM SKI-606 significantly suppressed phospho-CrkL levels, whereas a higher concentration of IM (5 μM) was needed to achieve a similar degree of suppression. Although treatment of CML CD34 + cells with IM was associated with increased p42/44 MAPK activity, a significant increase in MAPK activity was not observed when the same samples were treated with SKI-606. SKI-606 is therefore significantly more potent than IM in inhibiting Bcr-Abl TK in CML progenitors. Unlike IM, SKI-606 treatment was not associated with a significant compensatory increase in p42/44 MAPK signaling, which could potentially be beneficial in targeting malignant stem cells. Further investigation into the effects of SKI-606 on CML stem cells as a single agent or in combination with other compounds is warranted.